Kehidupan Doa untuk Mencapai Kemurnian Batin Berdasarkan Pemikiran Bapa-Bapa Suriah - Margareta Ruy; Hendi (LPPM STT Baptis Kalvari, 2024)
This research explores the importance of prayer in human life as a path to inner purity and a closer relationship with God. By aiming the prayer as an important life practice to open the path of reconciliation between man and God, the researcher uses a literature research method that examined the writings of the Syrian Fathers as a reference. The author synthesizes the book